Self-Replicating Catalyzed Hairpin Assembly for Rapid Signal Amplification - Dai, Jianyuan; He, Hongfei; Duan, Zhijuan; Guo, Yong; Xiao, Dan (Analytical chemistry (Washington), 2017)
A rapid signal amplification system based on the self-replicating catalyzed hairpin assembly is reported in which two hairpins, H1 and H2, were well-designed in which two split target/trigger DNA and two split G-quadruplex sequences were respectively integrated into H1 and H2. Target/trigger DNA can be cyclically used in this system to form the duplex DNA assemblies (H1-H2), which will bring the two G-quadruplex fragments into close-enough proximity to induce the formation of intact G-quadruplex as a colorimetric signal readout. Similarly, the two split target/trigger DNA sequences will reunite into a DNA sequence that is identical to the target/trigger DNA; then, the obtained replica can also be cyclically used as a new activator unit to trigger the CHA reaction, leading to the rapidly and significantly enhanced formation of target/trigger DNA replicas with the concomitant generation of a higher signal. This self-replication-based autocatalytic signal amplified approach has been successfully used to develop a rapid and visual assay for DNA and small molecule detection.